A case report of adult onset nephrotic syndrome in pregnancy - Budhewar, Amita; Ubale, Sunita; Senapati, Jaynarayan; Gurjar, Rakeshkumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Proteinuria in pregnancy is one of the most common issues encountered on a routine basis, mostly thought due to preeclampsia. However, there are plethora of reasons for proteinuria other causes of the same should also be thought while diagnosing and managing proteinuria. One of the causes of massive proteinuria is nephrotic syndrome. Nephrotic syndrome is a clinical syndrome defined massive proteinuria responsible for hypoalbuminemia resulting in hyperlipidemia edema and various complications. It is caused by increased permeability through damaged basement membranes in renal glomeruli. Nephrotic range of proteinuria defined as urinary loss of 3 gm or more protein/ 24 hours or presence of 2 gm of protein per gram of creatinine in spot urinary samples. Here is a case report of nephrotic syndrome in pregnancy managed by a multidisciplinary approach with successful outcome.